The semantic web -- ISWC 2017 : 16th International Semantic Web Conference, Vienna, Austria, October 21-25, 2017, Proceedings. Part I - d'Amato, Claudia, 1977- ; Fernandez, Miriam ; Tamma, Valentina ; Lecue, Freddy ; Cudré-Mauroux, Philippe ; Sequeda, Juan ; Lange, Christoph, 1980- ; Heflin, Jeff (Springer, 2020)
The two-volume set LNCS 10587 + 10588 constitutes the refereed proceedings of the 16th International Semantic Web Conference, ISWC 2017, held in Vienna, Austria, in October 2017. ISWC 2017 is the premier international forum, for the Semantic Web / Linked Data Community. The total of 55 full and 21 short papers presented in this volume were carefully reviewed and selected from 300 submissions. They are organized according to the tracks that were held: Research Track; Resource Track; and In-Use Track.Research Track: Multi-Label Based Learning for Better Multi-Criteria Ranking of Ontology Reasoners -- The Efficacy of OWL and DL on User Understanding of Axioms and Their Entailments -- A Decidable Very Expressive Description Logic for Databases -- Improving Visual Relationship Detection using Semantic Modeling of Scene Descriptions -- An Empirical Study on How the Distribution of Ontologies Affects Reasoning on the Web -- Expressive Stream Reasoning with Laser -- Semantics and Validation of Shapes Schemas for RDF -- Temporal Query Answering in DL-Lite over Inconsistent Data -- Semantic Wide and Deep Learning for Detecting Crisis-Information Categories on Social Media -- Tractable Query Answering for Expressive Ontologies and Existential Rules -- Zooming in on Ontologies: Minimal Modules and Best Excerpts -- Global RDF Vector Space Embeddings -- LDScript: a Linked Data Script Language -- Practical Update Management in Ontology-based Data Access -- Computing Authoring Tests from Competency Questions: Experimental Validation -- Matching Web Tables with Knowledge Base Entities: From Entity Lookups to Entity Embeddings -- Learning Commonalities in SPARQL -- Meta Structures in Knowledge Graphs -- Challenges of source selection in the WoD -- AMUSE: Multilingual Semantic Parsing for Question Answering over Linked Data -- Computing FO-Rewritings in EL in Practice: from Atomic to Conjunctive Queries -- A Formal Framework for Comparing Linked Data Fragments -- Language-agnostic Relation Extraction from Wikipedia Abstracts -- Alignment Cubes: Towards Interactive Visual Exploration and Evaluation of Multiple Ontology Alignments -- Attributed Description Logics: Ontologies for Knowledge Graphs -- Reliable Granular References to Changing Linked Data -- Cost-Driven Ontology-Based Data Access.-The Odyssey Approach for Optimizing Federated SPARQL Queries -- Automated Fine-grained Trust Assessment in Federated Knowledge Bases -- Completeness-aware Rule Learning from Knowledge Graphs -- Entity Comparison in RDF Graphs -- Provenance Information in a Collaborative Knowledge Graph: an Evaluation of Wikidata External References -- Strider: A Hybrid Adaptive Distributed RDF Stream Processing Engine -- Mining Hypotheses from Data in OWL: Advanced Evaluation and Complete Construction -- Semantic Faceted Search with Aggregation and Recursion -- Investigating learnability, user performance, and preferences of the path query language SemwidgQL compared to SPARQL -- Cross-lingual Entity Alignment via Joint Attribute-Preserving Embedding -- Blockchain Enabled Privacy Audit Logs -- VICKEY: Mining Conditional Keys on RDF datasets -- Ontolex JeuxDeMots and Its Alignment to the Linguistic Linked Open Data Cloud -- Towards Holistic Concept Representations: Embedding Relational Knowledge, Visual Attributes, and Distributional Word Semantics -- An extension of SPARQL for expressing preferences -- Encoding Category Correlations into Bilingual Topic Modeling for Cross-Lingual Taxonomy Alignment -- Cross-lingual infobox alignment in Wikipedia using Entity-Attribute Factor Graph.